Are Neighborhood Features Associated With Premature Mortality in Toronto Neighborhoods? (International Research in Economics and Finance, 2022)
Objective: The relationship between neighborhood social and economic features and the residents’ premature mortality rate is a controversial topic that has brought concerns from many local governments. The purpose of this paper was to determine the impacts of three indicators, including numbers of health providers, numbers of drug arrests, and neighborhood equity scores on premature mortality in the 140 neighborhoods in the City of Toronto. Methods: Conducting regression analysis by using the data from January 2018 to December 2018 obtained from OpenData Toronto. The number of health providers, which shows how many medical service sectors the local community has is generated into a dummy variable (